ETNOBOTANI MASYARAKAT DAYAK NGAJU DI DAERAH TIMPAH KALIMANTAN TENGAH - Francisca Murti Setyowati (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
The Ngaju, a Dayak tribe of Central Kalimantan, depend extensively onsurrounding natural resources for their food, medicines, cosmetics,construction materials, and other uses. A field study was conducted amongstthe Ngaju using direct observation and interviewing key persons includingcommunity leaders, traditional healers and local families. Based on the datacollected in the field, we recorded 107 plant species belonging to 51 familiesand 86 genera, used as food (56 species), medicine (46 species), cosmetics (4species), building material (9 species), and other uses (9 species). Severalspecies with potential economic value will be discussed in this paper, and localcustoms relating to traditions agriculture knowledge will be elaborated. Thepotency of the plants in connecting to the culture of the Dayak Ngaju will bealso be discussed in this paper. Three of the species studied consideredendangered species: Alyxia reinwardtii (Widjaja 1992), Eurycoma longifolia(Rifai 1992) and Cinnamomum sintoc (Widjaja 1992).